2001
DOI: 10.1097/00006565-200106000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ability of hospitals to care for pediatric emergency patients

Abstract: Emergent and critical care of infants and children may not be well integrated and regionalized within our health care system, suggesting that there is room for improvement in the quality of care for children encountering emergent illness and trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 12 publications
3
70
0
5
Order By: Relevance
“…Regionalization also contributes to the fact that rural and underserved hospitals and EDs frequently lack equipment, experience, and personnel with subspecialty training. 2,[34][35][36][37] The uneven distribution of resources and expertise 38,39 may explain some of our findings of varying odds of transfer for certain conditions, including pediatric cardiac services. 40,41 In summary, we found that pediatric patients without insurance or reported as having self-pay are statistically more likely to be transferred to another hospital for inpatient care than to be admitted locally compared with children with private insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Regionalization also contributes to the fact that rural and underserved hospitals and EDs frequently lack equipment, experience, and personnel with subspecialty training. 2,[34][35][36][37] The uneven distribution of resources and expertise 38,39 may explain some of our findings of varying odds of transfer for certain conditions, including pediatric cardiac services. 40,41 In summary, we found that pediatric patients without insurance or reported as having self-pay are statistically more likely to be transferred to another hospital for inpatient care than to be admitted locally compared with children with private insurance.…”
Section: Discussionmentioning
confidence: 99%
“…164,[176][177][178][179] This is especially true for infants and children with cardiovascular disease or illness. 180 In addition, the staff working in smaller, general EDs, including physicians, nurses, pharmacists, and support staff, are often less experienced in caring for children with congenital heart disease or other acquired cardiac conditions.…”
Section: Telecardiology In the Edmentioning
confidence: 99%
“…16 It has been shown that it is more difficult to obtain a history and conduct an examination on an anxious child. 17 Environmental constraints can have potentially adverse outcomes, as highlighted in a Korean study, which showed a correlation between overcrowding in cEDs and increased mortality. 18 …”
Section: Emergency Department Environmentmentioning
confidence: 99%